Mammoplasty Using Modified Superomedial Pedicle Technique in Severely Macromastia and Ptotic Breasts - Engin Selamioğlu; Özgür Agdoğan (The Breast Journal)
Mammoplasty is a surgery commonly used for macromastia. Many mammoplasty techniques are described, all with their specific pros and cons. However, the concern to avoid serious complications sometimes takes precedence, and the ideal result cannot be. For macromastia and severely ptotic breasts, usually the free nipple-areolar complex (NAC) mammoplasty technique is implemented. The results, however, may only be completely satisfactory regarding cosmetics. Loss of NAC, poor appearance, flabbiness, flattening, and ptosis are among the disadvantages of this technique. This study aimed to present the results of mammoplasty employing the superomedial pedicle technique without interrupting a macromastia central base with a pedicle length of 8 to 18 cm. According to the literature, many plastic surgeons recommend the free NAC rather than the pedicle technique because of the high complication rates in mammoplasties planned for highly ptotic breasts and macromastia. On the other hand, many free NAC techniques and their modifications with pedicle mammoplasty are described. The general conviction is that a standard method, protocol, or technique good for all patients does not exist. Our results are more acceptable both cosmetically and physiologically. Therefore, the superomedial pedicle technique can be modified to achieve ideal results where free NAC mammoplasty is considered for severe macromastia and ptotic patients. This combined method contributes to the viability of NAC by increasing blood supply to breast tissue and providing an ideal breast appearance.